Forage legume break crops in Australia and their tolerance to broadleaf herbicides - Sandral G.A.; Dear B.S. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
The intensification of the cropping phase in Australian ley and phased farming systems has lead to a demand for forage legumes that are tolerant or resistant to applied herbicides. The study described here identifies the herbicide tolerance of 12 forage legumes to 10 herbicides. It clearly shows that the cultivars Leeton (Trifolium resupinatum) and Antas (T. subterraneum var. brachycalycinum) were the most herbicide tolerant of the legumes tested and that Cefalu (T. vesiculosum) and Bigbee (T. alexandrium) were amongst the most sensitive. However the highest yielding legumes were Zulu (T. vesiculosum) and Caprera (T. incarnatum). The most phytotoxic herbicides identified were MCPA, Spinnaker and Tigrex while the safest herbicides were Treflan, Stomp, and Yield.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)